MSMEs' Perceptions of QRIS Use in Financial Transactions and Recording in Singaraja City - Sanjaya , Ketut; Masdiantini, Putu Riesty; Julianto, I Putu (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2025)
Some MSMEs do not fully understand the benefits and ease of using QRIS for financial transactions. Furthermore, the low utilization of QRIS in financial recording hinders the optimization of transparency and efficiency of business management. This study aims to analyze the perceptions of Micro, Small, and Medium Enterprises (MSMEs) in Singaraja City regarding using the Quick Response Code Indonesian Standard (QRIS) in financial transactions and recording. This study used a qualitative approach with in-depth interviews with five MSMEs actively using QRIS. Data were collected through observation, semi-structured interviews, and documentation, then analyzed using the Miles & Huberman model, including data reduction, data presentation, and conclusion. The results showed that most MSMEs viewed QRIS as an efficient, easy-to-use transaction tool that supports orderly financial recording. QRIS is considered to increase business professionalism, speed up transactions, and provide digital transaction evidence that can be integrated into the bookkeeping system. However, challenges exist, such as low digital literacy, limited internet access, and resistance from consumers who are not yet accustomed to digital payments. The implications of this research indicate that the success of QRIS implementation depends on increased digital education, infrastructure improvements, and ongoing support from financial institutions and local governments. This research contributes to understanding the adoption of digital payment technology in semi-urban areas and supports a more modern and transparent financial transformation for MSMEs.